“THE ROLE OF PRAGMATICS IN SPEECH INTERPRETATION: FROM SPEECH ACT THEORY TO COMMUNICATION PRACTICE”: THE ROLE OF PRAGMATICS IN SPEECH INTERPRETATION: FROM SPEECH ACT THEORY TO COMMUNICATION PRACTICE” - Akimbekova, Kuralay (Журнал иностранных языков и лингвистики, 2025)
As a student of linguistics and translation studies, I have long been fascinated by how people understand each other—not just through words, but through intentions, tone, and shared cultural knowledge. Language, in my view, is not merely a vehicle for conveying facts; it is a tool for doing things, for building relationships, for influencing others, and for negotiating meaning.